Design of a customized humanoid robot with coevolution of body morphology and its locomotion. Issue 9 (14th September 2022) - Zhang, Jiwen; Shi, Xunlei; Fu, Chenglong; Liu, Li; Chen, Ken
Abstract: An important goal for humanoid robots is to achieve fast, flexible and stable walking. In previous research, the structure and walking algorithms evolved separately, resulting in a slow evolution speed and lack of an initial design basis. This paper proposes comprehensively considering body morphology and walking patterns, exploring the relationship between them and their influence on the motion ability. The method parameterizes the body morphology and walking patterns. Then a response surface model is established to describe the complex relationship between these parameters and finally obtain the optimized parameters, which provides a reference for the structural design and gait generation.